The patterns of educational leadership of the public schools headteachers in the middle of Jeddah and the extent of motivation to work of the primary classes teachers from the teachers point of view - Al-Juhani, Hanan Jaber Attia Jaber (Journal of Educational and Psychological Sciences, 2022)
The study aimed to know the impact of the democratic pattern on the primary school teachers and their degree of motivation towards work. The study uses the descriptive analytical method, as well as a questionnaire on (220) female teachers. The most important results are: Most of primary school leaders in the area of central Jeddah practice a highly democratic leadership style , some primary school leaders practice the autocratic and moderately lenient style of primary school , the level of motivation of primary school teachers to work in primary schools is very high when they practice democratic leadership , the level of ambition , management and perservance of the first grade teachers in primary schools in central Jeddah , one of the most important recommendations of the study: The study recommends education offices and supervision departments to support activity program for primary school leaders in the center of Jeddah to train them on all kinds of leadership patterns , so that the appropriate leadership pattern is chosen for the school administration. The study also recommends supervisory offices to strengthen leadership practices for leaders of primary schools in the city of Jeddah that activates the democratic style because of its positive correlation with the level of motivation towards working with female teachers in all fields.
Keywords: leadership patterns; pedagogical leadership; motivation; public schools; leaders; teachers